سفارتی تعلقات کے لیے پیغمبرانہ حکمت عملی اور اس کی معاصر معنویتProphetic Strategy to Diplomatic Relations and Its Contemporary Significance (Al-Qamar, 2020)
The significance of diplomatic relations is undeniable and absolute in the contemporary age. It is almost impossible for a nation to survive without tying bonds with neighboring countries. Materialistic gains have received a lot of consideration in the modern-day global relations framework, while morality and faiths have been overlooked.  In Islam, diplomacy is much more than just gaining benefits for the country. From an Islamic perspective, the broad laws of diplomacy and the method in which the Islamic sovereign interacts with other countries and organizations will be studied in this article. Diplomacy in Islam is preferable to exchange material benefits and privileges since its goal is to achieve human enlightenment through heavenly precepts. Ultimately, the Islamic regime views other nations as brothers or neighbors striving to organize ties, rather than as a source of oppression. The Seerah of Holy Prophet (PBUH) provides an extensive and comprehensive diplomacy pattern to foster harmony and international relation. By applying descriptive and qualitative research methods, this article will highlight the Prophetic approach to diplomatic relations that stipulates a framework to harmonize and systematize contemporary international relations.
Keywords: Diplomatic Relations; Prophetic Strategy; Contemporary Significance